Optimal power scheduling strategy in power systems using swarm optimization technique - Kamari N.A.M.; Rahmat N.A.; Musirin I. (World Academy of Research in Science and Engineering, 2023)
This study proposes a power scheduling strategy for power system networks by using PSO technique. This strategy searches for the optimal power for each generating unit in the system, without compromising the total power demands and constraints of each unit. The objective function aims to minimize the total generation cost. The amount of power loss is measured to determine the feasibility of the proposed technique. In addition, optimization processes using evolutionary programming (EP) and artificial immune system (AIS) are implemented. Five-and 30-bus power system networks are selected and processed using MATLAB. The simulation results indicate that PSO performs better than EP and AIS in determining the optimal power generation value with minimum generation cost and power loss. 2019, World Academy of Research in Science and Engineering. All rights reserved.